2019
DOI: 10.1021/acs.jmedchem.9b01069
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrinoid–Cyclodextrin Assemblies in Biomedical Research: An Update

Abstract: Porphyrinoids, well-known cofactors in fundamental processes of life, have stimulated interest as synthetic models of natural systems and integral components of photodynamic therapy, but their utilization is compromised by self-aggregation in aqueous media. The capacity of cyclodextrins to include hydrophobic molecules in their cavity provides porphyrinoids with a protective environment against oxidation and the ability to disperse efficiently in biological fluids. Moreover, engineered cyclodextrin−porphyrinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 176 publications
(311 reference statements)
0
20
0
Order By: Relevance
“…The distortions are not transitory in nature and lead to formation of assemblies which are stable even at high temperatures. The structure and properties of cyclodextrins continue to inspire chemists [39–46] . In this context the understanding that CD structures are not inflexible may lead to design of novel molecular architectures in the future.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distortions are not transitory in nature and lead to formation of assemblies which are stable even at high temperatures. The structure and properties of cyclodextrins continue to inspire chemists [39–46] . In this context the understanding that CD structures are not inflexible may lead to design of novel molecular architectures in the future.…”
Section: Methodsmentioning
confidence: 99%
“…The structure and properties of cyclodextrins continue to inspire chemists. [39][40][41][42][43][44][45][46] In this context the understanding that CD structures are not inflexible may lead to design of novel molecular architectures in the future. Structural deformation of cyclodextrin is subject to several theoretical studies, but none of the studies have considered large deformations to its structure.…”
mentioning
confidence: 99%
“…Compared to other synthetic host systems, e.g., crown ethers [ 7 , 8 , 9 ], calixarenes [ 10 , 11 , 12 ], cucurbiturils [ 9 , 13 , 14 ], and pillararenes [ 15 , 16 , 17 ], CDs are less toxic and/or exhibit good water solubility and biocompatibility [ 11 , 18 ]. Their facile covalent modification also renders them highly promising candidates as functional delivery systems [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biomedical applications of the supramolecular Por/CD Me system have been demonstrated by us and other research groups and reviewed in recent papers. [13][14][15][16][17] We recently investigated selective detection with the Por/CD Me complex in biological media, including serum, blood, and urine, using 5,10,15,20-tetrakis(4-sulfonatophenyl) porphyrin (TPPS) and 13 C-labeled heptakis(2,3,6-tri-O-methyl-13 C)-β-cyclodextrin ( 13 C-CD Me ). [18] Several NMR techniques revealed that the supramolecular 1 : 2 TPPS/ 13 C-CD Me complex is quite stable and detectable in these biologically crowded media, that contain many biocomponents, including proteins and lipids.…”
Section: Introductionmentioning
confidence: 99%